The Application of CEFR Standard Framework in Enhancing Communicative English Competencies: The Bibliometric Analysis and Its Support to Sustainable Development Goals (SDGs) - Nadtayay, Nawaporn; Wongsaphan, Montree; Wu, Chicheng (International Journal of Language Education, 2025)
This study investigates the impact of CEFR-based frameworks on communicative English language teaching models in Thailand’s primary education sector from 2020 to 2024. Addressing the global call for standardized language proficiency, the research aims to map thematic trends and conceptual developments within CEFR-aligned pedagogy. A quantitative bibliometric method was employed, analyzing 500 scholarly articles from Google Scholar using descriptive statistics and VOSviewer-generated visualizations. Results show a research peak in 2022, followed by a sharp decline in 2024, indicating either shifting national priorities or saturation in CEFR-focused studies. Core terms like “proficiency,” “communication,” and “task-based learning” emerged consistently, reflecting CEFR’s central role in curriculum reform, instructional design, and digital integration. Because gaps remain in measuring learner outcomes and contextual implementation, the study reveals areas for further empirical and localized research. This work contributes to understanding CEFR’s transformative role and encourages more strategic, evidence-based applications in English language education policy and practice in Thailand. This study supports current issues in sustainable development goals (SDGs).